PENGARUH FINANCIAL LITERACY, KEBIJAKAN MODAL MINIMAL INVESTASI DAN HUBUNGAN PERTEMANAN TERHADAP KEPUTUSAN BERINVESTASI DI PASAR MODAL PADA MAHASISWA DI KOTA PEKANBARU - Damayanti Damayanti Rahayu; Rokhmawati Andewi; Fitri Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to examine the effect of Financial Literacy, Minimum CapitalInvestment Policy and Friendship Relationships on Investment decisions in theCapital Market. This type of research is quantitative. The population in this studywere students who not invested in Pekanbaru. The data collection in this studyused the questionnaire method. The data analysis techniques used in this researchstudy using the multiple Regression with the help of the SPSS program. Theresults of the study show that: Financial literacy, minimum investment capital,and friendship have a significant effect on investment decisions. Keywords : literacy, minimal capital, friendship, decisions